Improving Intercultural Learning through the Orientation of Sojourners. AFS Occasional Papers in Intercultural Learning, No 1 - Grove, Cornelius Lee.; AFS International/Intercultural Programs, Inc., New York, NY. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1982)
Cross-cultural orientation programs are generally intended to help sojourners in countries with cultures that are different from their own to make practical preparations for living abroad; communicate with people in the host country; avoid social errors; refrain from judging the host culture against their own cultural norms; and cope with culture shock. Many of such programs have merit in that they are well planned and well implemented; however, a more important concern should be whether these programs have worth in improving sojourners' abilities to learn about other cultures on their own. In considering the worth of orientation programs, issues often emerge concerning who should be included in training; the emphasis of programs; orientation approaches to use; and the need to train returnees to the home culture. Theory and past experience suggest that program worth may be enhanced by (1) providing training not only for participants but also for their host families and natural families; (2) emphasizing post-arrival (in the host country) orientation while retaining pre-departure orientation; (3) increasing knowledge of the home culture along with training oriented toward the host culture; (4) employing both culture-general and culture-specific approaches; (5) providing reorientation programs for returnees to the home culture; and (6) utilizing both experiential and intellectual approaches in training. (Author/MJL)
Availability: AFS International/Intercultural Programs, 313 East 43rd Street, New York, NY 10017 (no charge).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Cross Cultural Training; Cultural Awareness; Cultural Differences; Culture Conflict; Exchange Programs; Family Involvement; Intercultural Programs; Training Methods; American Field Service; Opinion Papers